MINLP model for the detailed scheduling of refined products pipelines with flow rate dependent pumping costs. (2nd January 2015) - Cafaro, Vanina G.; Cafaro, Diego C.; Méndez, Carlos A.; Cerdá, Jaime
Highlights: Scheduling multiproduct pipelines to transport fuels from refineries to terminals. Novel MINLP model for pipeline scheduling with detailed energy consumption. New nonlinear equation to estimate the pump power required for transportation . Real-world case studies successfully solved using GAMS–DICOPT algorithm. Reductions achieved by keeping a more stable flow rate profile. Abstract: Multiproduct pipelines transport fuels from refineries to distant distribution terminals in batches. The energy needed to move the fluids through the pipeline is mainly associated with elevation gradients and friction head loss. Commonly, friction loss is the major term requiring pump stations to keep the flow moving, and it is strongly dependent on the fluid flow rate. Some studies have been carried out for reducing the pumping costs in multiproduct pipelines, but none of them has been focused on thoroughly considering the head loss due to friction along the pipeline. This paper introduces a novel MINLP continuous-time formulation for the detailed scheduling of single-source pipelines, rigorously tracking power consumption at every pipeline segment through nonlinear equations. Real-world case studies are successfully solved using GAMS–DICOPT algorithm, which proves to be a useful tool for solving large-scale, nonlinear scheduling problems. Important reductions in the operation costs are achieved by keeping a more stable flow rate profile over the planning horizon.